2019
DOI: 10.3389/fmicb.2019.02850
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cell Division Regulated by DicC With the Formation of Viable but Non-culturable Escherichia coli O157:H7

Abstract: The viable but non-culturable (VBNC) state, in which bacteria fail to grow on routine culture media but are actually alive, has been widely recognized as a strategy adopted by bacteria to cope with stressful environments. However, little is known regarding the molecular mechanism of VBNC formation. Here, we aimed to elucidate the specific roles of cell division regulatory proteins and the cell growth rate during VBNC Escherichia coli O157:H7 formation. We have previously found that expression of dicC is reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 60 publications
(79 reference statements)
1
6
0
Order By: Relevance
“…Recent work in E. coli O157:H7 showed that overexpression of DicC repressed dicA's transcription, similar to Cro repression of cI (39). Additionally, deletion of dicC led to a reduction in dicB levels while overexpression induced dicB expression (39). Our results show that DicC is important for the spontaneous induction phenotype of dicBp, as deletion of dicC results in a reduction in the frequency of cells that have induced dicBp.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Recent work in E. coli O157:H7 showed that overexpression of DicC repressed dicA's transcription, similar to Cro repression of cI (39). Additionally, deletion of dicC led to a reduction in dicB levels while overexpression induced dicB expression (39). Our results show that DicC is important for the spontaneous induction phenotype of dicBp, as deletion of dicC results in a reduction in the frequency of cells that have induced dicBp.…”
Section: Discussionsupporting
confidence: 74%
“…A study by Yun et al in E. coli MG1655 showed that by binding to dicCp, DicA blocks dicC transcription and activates its own transcription (47). Recent work in E. coli O157:H7 showed that overexpression of DicC repressed dicA's transcription, similar to Cro repression of cI (39). Additionally, deletion of dicC led to a reduction in dicB levels while overexpression induced dicB expression (39).…”
Section: Discussionmentioning
confidence: 86%
“…In our study, the sulA gene was significantly upregulated as shown in Figure 2g. DicB is another cell division inhibition protein, [ 53 ] which was also significantly upregulated in E . coli treated with EPGNs (Figure 2g).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the sulA gene was significantly upregulated as shown in Figure 2g. DicB is another cell division inhibition protein, [53] which was also significantly upregulated in E. coli treated with EPGNs (Figure 2g). All these results showed that the cell division of E. coli was largely inhibited by the treatment of EPGNs, confirming the cell division inhibitory effect of EPGNs.…”
Section: Epgns Cause Bacterial Cell Expansionmentioning
confidence: 98%
“…Log phase bacteria were used to focus population gates around E. coli or S. aureus cells that were alive and had intact cell membrane. Data were collected using CellQuest software (Becton Dickinson, San Jose, CA, United States; Pan et al, 2019).…”
Section: Fcm Analysismentioning
confidence: 99%